Working conditions and the health of workers: An elaboration of a responsible prevention ratio. (November 2017) - Sirven, Nicolas; Cardebat, Jean-Marie; Coupaud, Marine
The coincidence between trends in the decline of workers' health and the increasing practice of Corporate Social Responsibility (CSR) seems a paradox. Using data from the French Employment Survey 2005, in this article the authors develop an index of responsible prevention by combining a score of severity of working conditions with a score of risk prevention at the workplace. The authors then explore the influence of this variable on the propensity to stop working for medical reasons. The results show that prevention increases workers' health status and suggest the existence of an optimal level of social CSR expenditure.